Prospective study of the effect of auricular percutaneous electrical nerve field stimulation on quality of life in children with pain related disorders of gut-brain interaction - Chogle, Ashish; Visnagra, Kaajal; Janchoi, Jamie; Tran, Tammy; Davis, Rachel; Callas, Nicole; Ornelas, Elisa (Frontiers in Pain Research, 2023)
Background Disorders of the Gut-Brain Interaction (DGBIs) account for 50% of pediatric gastrointestinal (GI) consultations. Children with DGBIs have worse quality of life (QoL) than those with organic GI disorders such as inflammatory bowel disease and gastroesophageal reflux disease. Pediatric DGBIs patients, especially those with chronic abdominal pain (AP), have impaired QoL and increased psychological distress in the form of anxiety and depression. Percutaneous Electrical Nerve Field Stimulation (PENFS) therapy has been shown to be effective in improving symptoms and functioning in children with DGBIs. The treatment's impact on these patients' QoL is unknown. Methods This prospective study evaluated changes in QoL, gastrointestinal symptoms, functional disability, somatization, global health, anxiety, and depression in patients aged 11–18 years who received PENFS therapy (IB-stim, NeurAxis, Versailles, IN) for treatment of pain related DGBIs, once a week for four consecutive weeks. Results This study included 31 patients with an average age of 15.7 years (SD = 2); 80.6% were female. After PENFS therapy, patients reported significant reductions in abdominal pain, nausea severity, functional disability, somatization, and anxiety from baseline to week 4 (p < 0.05). Parents reported significant improvement in their child's QoL regarding physical function, psychosocial function, and generic core scale scores (p < 0.05). Parents also noted reduced abdominal pain, functional disability, and somatization. Average scores on the Patient-Reported Outcomes Measurement Information System (PROMIS) Global Health scale significantly improved based on both patient and parent reports (p < 0.05). Our patients' QoL was significantly lower than healthy controls at baseline and after treatment (p < 0.05). Conclusion Our research demonstrates that PENFS significantly enhances the QoL of children suffering from pain-related DGBIs, in addition to improvement in GI symptoms, daily functioning, somatization, global health, and psychological comorbidities. These findings demonstrate the effectiveness of PENFS and its potential to alleviate the suffering of countless children.